Poetry on Military Subjects in Modern Media Space: Linguistic-Cognitive and Modal-Pragmatic Interpretation - Kostusiak, Nataliia M.; Коnstankevych, Iryna M.; Shulska, Nataliia M.; Bukina, Nataliia; Pavlyuk, Ihor; Iaruchyk, Viktor; Mitchuk, Olha; Shumenko, Olha; Oliinyk, Nataliia; Reznichenko, Yuliia (My University, 2024)
The article comprehensively characterizes the war-themed poetry presented in the modern media space, emphasizing its features such as neorealism, conciseness, sensuality, aesthetic diversity, and its focus on understanding the depth of today’s realities. Involvement of the linguistic-cognitive and modal-pragmatic aspect in the analysis made it possible to focus attention on the ideological-thematic and figurative- symbolic originality of the poetic work of Volyn writers, to interpret the intentions laid down by them, to outline various psychological states, feelings, and emotional experiences. It was found that the authors use metaphors, epithets, similes, elements of allusion and reminiscence, which give the texts evaluative and emotionally expressive color. Emphasis is placed on a new interpretation of the images of the native land, sky, sun, seasons, environment, the description of which involves phytonominals, zoonames, and other lexemes; markers of the Christian faith adapted to the communicative and pragmatic needs of war-themed works were revealed. The updated textual links of the lexeme children are traced, psychologically marked means of authentic reflection of brutal war realities tangential to this problem are determined. Against the background of negative pictures of the war, poetic lines full of optimism, a sense of invincibility, and faith in the revival of Ukraine are considered.
Keywords: lyrics; war; connotative aspect; image; symbol; allusion; reminiscence; intertextuality